Polyomavirus middle T antigen induces ribosomal protein S6 phosphorylation through pp60c-src-dependent and -independent pathways. - Talmage, D A (1988)
Phosphorylation of ribosomal protein S6 is elevated in polyomavirus-infected cells. This elevation results only in part from activation of S6 kinase activity. These effects appear to reflect independent activities of wild-type middle T antigen. Hr-t mutant NG59, encoding a defective middle T protein, and mutant Py808A, encoding no middle T protein, were unable to induce S6 kinase activity or elevate S6 phosphorylation. Two other site-directed mutants encoding altered middle T proteins did elevate S6 phosphorylation while only weakly stimulating S6 kinase activity. These results suggest at least two independent pathways leading to elevation of S6 phosphorylation. One pathway leads to induction of S6 kinase activity following activation of pp60c-src by transformation-competent middle T antigen. Another pathway operates independently of S6 kinase induction and can be regulated by transformation-defective middle T mutants such as Py1387T. This mutant, encoding a truncated middle T protein that failed to associate with the plasma membrane and to activate pp60c-src, caused increased levels of S6 phosphorylation without detectably increasing S6 kinase activity. The ability of mutants such as Py1387T to induce S6 phosphorylation correlated with their ability to increase phosphorylation of VP1, an event linked to maturation of infectious virions.